Assessing the Growth of Ethical Banking: Some Evidence from Spanish Customers - Callejas-Albiñana, Fernando E.; Martínez-Rodríguez, Isabel; Callejas-Albiñana, Ana I.; de Vidales-Carrasco, Irene M. (Frontiers in Psychology, 2017)
Aristotle, who, having predated Adam Smith by 2000 years, deserves to be recognized as the world’s first economist (Solomon, 1995), distinguished between two different senses of what we call economics: oikonomikos, or household trading, which he approved of and considered essential to the working of any even slightly complex society, and chrematisike, or trade for profit, which he considered selfish and utterly devoid of virtue, calling those who engaged in such practices “parasites.” Of course, consumers do not purchase and invest for solely economic reasons (Polanyi, 1944). Interest in ethics in economics has been the subject of continuous study. In this regard, the recent financial crisis has had not only economic, but also social, psychological, political, and ethical consequences, which have impacted the financial and banking system. Consumers are no longer drawn only by the economic return but also by ethical factors. Ethical banking is on the rise. This paper aims to explain the reasons for the growth in ethical banking and to answer the following questions: can banking consumers-investors change the characterization of the banking system? Can ethical banking gain ground on traditional banking? And is ethical banking really effective? To this end, it will examine the Spanish case, using econometric causal regression models to identify the reasons why consumers decide to invest in ethical banking and determine its role in the Spanish economy.